Transforming places : lessons from Appalachia - Fisher, Stephen L., 1944-; Smith, Barbara Ellen, 1951- (University of Illinois Press, 2012)
"In this era of globalization's ruthless deracination, place attachments have become increasingly salient in collective mobilizations across the spectrum of politics. Like place-based activists in other resource-rich yet impoverished regions across the globe, Appalachians are contesting economic injustice, environmental degradation, and the anti-democratic power of elites. This collection of seventeen original essays by scholars and activists from a variety of backgrounds explores this wide range of oppositional politics, querying its successes, limitations, and impacts. The editors' critical introduction and conclusion integrate theories of place and space with analyses of organizations and events discussed by contributors. Transforming Places illuminates widely relevant lessons about building coalitions and movements with sufficient strength to challenge corporate-driven globalization."--Publisher's website
Keywords: Community organization -- Appalachian Region.; Social action -- Appalachian Region.; Political participation -- Appalachian Region.; Appalachian Region -- Social conditions.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; BUSINESS & ECONOMICS -- Economics -- Comparative.; POLITICAL SCIENCE -- Economic Conditions.; HISTORY -- Social History.; Community organization; Political participation; Social action; Social conditions; Appalachian Region